DESKRIPSI MISKONSEPSI SISWA PADA MATERI ATOM, MOLEKUL, DAN ION DI SMP NEGERI 21 PONTIANAK - Anggraeni, Vanny; Enawaty, Eny; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to determine misconception of studentand to describe the causes of the misconceptin in atoms, molecules, and ions material on grade VIII F SMPN 21 Pontianak.. This reaserch type is qualitative research with descriptive method. The sample that used is 37 students. The instrument of this research was diagnostic test that organized as multiple choice with three answer alternative. The instrument used reason accompanied by Certainty of Response Index (CRI) and interview to students who misconception about atoms, molecules, and ions. Research result showed that misconception found in definition of atom by Thomson theory (78,4%), kinds of molecules (8,1%), relation of electron configuration and ions (21,6%), ions determination (21,6%), monoatomic (16,2%), poliatomic (83,8%), positive ions (8,1%) and negative ions (5,4%). According result of research that mean of student who misconception 24,32%. The most common misconceptions is polyatomic ions concept. These result show that the studentâ€™s misconceptions happened because of assosiative thinking student, intuition thinking, and ability of student with percentage are 4,38%, 34,21% and 61,4%.Keywords: misconception, certainty of response index (CRI), diagnostic testÂ